Understanding the Adoption Process of National Security Technology: An Integration of Diffusion of Innovations and Volitional Behavior Theories. Issue 11 (1st March 2017) - Iles, Irina A.; Egnoto, Michael J.; Fisher Liu, Brooke; Ackerman, Gary; Roberts, Holly; Smith, Daniel
Abstract: After the 9/11 terrorist attacks, the U.S. government initiated several national security technology adoption programs. The American public, however, has been skeptical about these initiatives and adoption of national security technologies has been mandated, rather than voluntary. We propose and test a voluntary behavioral intention formation model for the adoption of one type of new security technology: portable radiation detectors. Portable radiation detectors are an efficient way of detecting radiological and nuclear threats and could potentially prevent loss of life and damage to individuals' health. However, their functioning requires that a critical mass of individuals use them on a daily basis. We combine the explanatory advantages of diffusion of innovation with the predictive power of two volitional behavior frameworks: the theory of reasoned action and the health belief model. A large sample survey ( N = 1, 482) investigated the influence of factors identified in previous diffusion of innovation research on portable radiation detector adoption intention. Results indicated that nonfinancial incentives, as opposed to financial incentives, should be emphasized in persuasive communications aimed at fostering adoption. The research provides a new integration of diffusion of innovation elements with determinants of volitional behavior from persuasion literature, and offers recommendations on effective communication about new security technologies to motivate public adoption and enhance national safety.